2011
DOI: 10.1016/j.drugalcdep.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance and the effects of extended-release zolpidem during cannabis withdrawal

Abstract: Background Sleep difficulty is a common symptom of cannabis withdrawal, but little research has objectively measured sleep or explored the effects of hypnotic medication on sleep during cannabis withdrawal. Methods Twenty daily cannabis users completed a within-subject crossover study. Participants alternated between periods of ad-libitum cannabis use and short-term cannabis abstinence (3 days). Placebo was administered at bedtime during one abstinence period (withdrawal test) and extended-release zolpidem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
101
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 46 publications
7
101
1
3
Order By: Relevance
“…Similar observations were made by Vandrey, who also noted decreased sleep efficiency and increased sleep latency among 20 subjects in a controlled laboratory study. 10 An increase, rather than reduction in REM sleep was observed in the Vandrey study. It is uncertain whether the differences between these studies were due to participant variations or research-design differences.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Similar observations were made by Vandrey, who also noted decreased sleep efficiency and increased sleep latency among 20 subjects in a controlled laboratory study. 10 An increase, rather than reduction in REM sleep was observed in the Vandrey study. It is uncertain whether the differences between these studies were due to participant variations or research-design differences.…”
mentioning
confidence: 84%
“…[5][6][7][8] There is some evidence that pharmacotherapy during cannabis abstinence attenuates withdrawal related sleep disturbances, 9 including improvements in polysomnographic measures of sleep effi ciency (but not latency) with the nonbenzodiazepine GABA(A) receptor agonist zolpidem. 10 While there is a plethora of studies exploring self-reported sleep disturbances associated with cannabis withdrawal, there are very laboratory study examining the muscle relaxant baclofen and the antidepressant mirtazapine. 11 Mirtazapine improved sleep but was not effective in relation to withdrawal symptoms or relapse rates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…42 Zolpidem was found to normalize sleep efficiency and improved self-reports of sleep quality, but had no effect on sleep latency abnormalities common in cannabis withdrawal. 43 Nitrazepam improved several objective sleep-related abnormalities but was not effective in improving subjective sleep symptoms. This may indicate that sedatives and/or hypnotics are an effective class to help with sleep-related abnormalities associated with cannabis withdrawal, but further research is required and likely this class of medication should be limited to the withdrawal period (i.e.…”
Section: Treatment Of Withdrawalmentioning
confidence: 98%